PaR1 secreted by the type IX secretion system is a protective antigen of Riemerella anatipestifer - Wang, Jialing; Chen, Yan; He, Xiaohua; Du, Xiaoli; Gao, Yongheng; Shan, Xinggen; Hu, Zhiqun; Hu, Qinghai (Frontiers in Microbiology, 2023)
Riemerella anatipestifer mainly infects domestic ducks, geese, turkeys, and other birds, and causes considerable economic losses to the global duck industry. Previous studies have shown that concentrated cell-free culture filtrates of R. anatipestifer induce highly significant protection against homologous challenge. In this study, 12 immunogenic proteins were identified in the culture supernatant of R. anatipestifer strain Yb2 with immunoproteomic analysis. Of these, three immunogenic proteins, AS87_RS06600 (designated ‘PaR1’ in this study), AS87_RS09020, and AS87_RS09965, which appeared in more than three spots on the western-blotted membrane, were expressed in Escherichia coli and purified. Animal experiments showed that the recombinant PaR1 (rPaR1) protein protected 41.67% of immunized ducklings against challenge with virulent Yb2, whereas rAS87_RS09020 or rAS87_RS09965 did not, and that ducklings immunized once with rPaR1 were 20%, 40%, and 0% protected from challenge with R. anatipestifer strains WJ4 (serotype 1), Yb2 (serotype 2), and HXb2 (serotype 10), respectively. In addition, rPaR1 immunized rabbit serum showed bactericidal activity against strain Yb2 at a titer of 1: 8. These results indicate that rPaR1 of strain Yb2 protects against homologous challenge. Amino acid homology analysis show that PaR1 is a non-serotype-specific protein among different R. anatipestifer serotypes. Furthermore, PaR1 is mainly secreted outside the cell through the T9SS, and is also located on the inner membrane of R. anatipestifer cells. Overall, our results demonstrate that R. anatipestifer PaR1 is a non-serotype-specific protective protein secreted by the T9SS.